Prevalence of sensitization to food allergens and challenge proven food allergy in patients visiting allergy centers in Rawalpindi and Islamabad, Pakistan - Inam, Muhammad (Springerplus, 2016)
In this study, we estimated the prevalence of food allergy in the adult allergic patients of Rawalpindi and Islamabad , Pakistan, based on self-report, skin prick test (SPT) and oral food challenge test (OFC). SPT was used for the estimation of sensitization to wheat, egg, milk, beef, chicken, mutton, fish, corn, lentils, rice, soya, peanut and banana. Among 689 patients, 39.19 % showed sensitivity to one or more foods, where, sensitization to wheat (156; 22.6 %) was highest, followed by egg (148; 21.48 %) and milk (138; 20.03 %). Sensitization to various proteins ranged between 15.53–15.97 %, while lentils, corn, rice, soya and peanut sensitization was 15.4, 16, 12.5, 12 and 11.5 % respectively. Only 7.1 % patients were SPT positive for banana allergen. SPT was performed in patients with self-reported food allergy (341/689) and also with no self-reported history of food allergy (348/689). SPT results were positive in 69.8 % of the self-report group, whereas, in the patients with no self-reported food allergy 9.2 % were found sensitized to one or more tested food allergens. 101 patients were recruited for OFC, 61 % of these were confirmed of food allergy. The prevalence of food allergy in the study population was 9 %. Food specific OFC results show that wheat allergy is affecting 1.6 % (95 % CI 0.9–2.84 %) of the total allergy patients, followed by egg allergy 1.31 % (95 % CI 0.70–2.47 %). Furthermore, corn allergy, rice allergy and peanut allergy were 1.02, 0.87 and 0.73 %, respectively. In conclusion, wheat allergy is the most prevalent, followed by egg, chicken, beef and fish allergy, respectively.